PERILAKU PENCARIAN INFORMASI DALAM PENYUSUNAN SKRIPSI MENGGUNAKAN AKUN TIKTOK @WIFAU OLEH MAHASISWA PROGRAM STUDI PERPUSTAKAAN DAN ILMU INFORMASI ANGKATAN 2021 UNIVERSITAS NEGERI PADANG - Rahmat Arif; Gustina Erlianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the information-seeking behavior of students in writing their undergraduate theses by utilizing content from the TikTok account @wifau. The research employs a descriptive quantitative approach with a survey method. The population consists of 89 students from the Library and Information Science Program at Universitas Negeri Padang, class of 2021, selected using a total sampling technique. Data were collected using a closed-ended questionnaire based on five key indicators of information-seeking behavior: information need identification, information seeking strategy, evaluation and selection of information, use of information, and ongoing search. The results show that students actively use TikTok as an initial source of information that triggers awareness of their information needs, helps develop search strategies, and supports the writing process. TikTok, especially the @wifau account, plays a significant role as an alternative medium that fosters students’ information literacy. This study indicates a shift in students’ information-seeking patterns toward the use of dynamic and visual-based social media. The findings contribute to a better understanding of how informal digital platforms are integrated into academic information behavior, suggesting new opportunities for educators and information professionals to support learning through relevant social media content